Bentonitas modificadas com organocátions, metais de transição e silano aplicadas como adsorventes para corantes aniônicos e como materiais hidrofóbicos - Brito, Deoclecio Ferreira de (2019)
Hybrids based on bentonite modified with organic cations, transition metals and silane were synthesized by different routes of synthesis and characterized by XRD, thermogravimetric analysis (TG), FTIR, XRF, TEM, SEM, elemental analysis CHN, analysis of the zeta charge potential and UV-Vis the solid state, evidencing the effective formation of the desired solids. Organobentonites were synthesized by microwave heating using three different surfactants (tetra, hexa and octadecyltrimethylammonium) with different carbon chain sizes and the modifications occurred in the bentonite structure were studied and the solids obtained were applied and evaluated in the adsorption of remazol blue RN anionic dye and the adsorption of a mixture containing three different types of anionic dyes and inorganic salts, both having satisfactory results, reaching approximately 100% of dye removal. Modified bentonites were also synthesized with the first series of transition metals (Fe2+, Fe3+, Co2+, Ni2+, Cu2+ and Zn2+) by the ion exchange process using conventional route, studying the changes occurred in the bentonite structure after incorporation and the solids were subsequently applied in the adsorption of the remazol blue RN anionic dye, for the iron-containing solids presented better adsorption results. Some factors were evaluated that may significantly influence the adsorption capacity, such as pH, adsorbent dosage, contact time and initial concentration of the dye solution. Finally, bentonites were silanized with 3-chloropropyltrimethoxysilane and submitted to subsequent reactions with 2-aminothiazole and 2-thiazoline-2-thiol in order to obtain hydrophobic materials. The hydrophobic character of the hybrids obtained by the subsequent reactions was confirmed by the wettability test by calculating the contact angle. All the results were promising, suggesting scientific and technological potential for the solids presented here.